2014
DOI: 10.4025/actascibiolsci.v36i1.21039
|View full text |Cite
|
Sign up to set email alerts
|

<b> Influence of cage farming on feeding and reproductive aspects of <i>Pimelodus maculatus</i> Lacépède, 1803 (Siluriformes: Pimelodidae) in the Chavantes reservoir, Brazil </b> - doi: 10.4025/actascibiolsci.v36i1.

Abstract: ABSTRACT. This study evaluated the diet and reproductive aspects of the population of Pimelodus maculatus around net cage fish farming in order to assess the possible impacts of this activity. Monthly collections were performed from March 2008 to February 2009 on two populations: one close to the net cages (NC) and one from an area not influenced by these cages denominated the "reference site" (RS). Results of the Alimentary Index (AI), Gonadosomatic Index (GSI), reproductive potential and histological analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Our results support that the favoring of few species around cage fish farms, contribute to spatial differences in fish community between fish farm and reference sites, as demonstrated by Permanova analysis. This favoring is supported by concomitantly studies performed in the same cage fish farms with the same fishes used in this study showed that opportunistic and omnivore species, like A. affinis, A. lacustris, I. labrosus, P. maculatus and S. insculpta consume the uneaten food released by fish farms, causing alterations in their numeric abundance, condition factor and reproductive period (Brandão et al, 2014;Brandão et al, 2013;Brandão et al, 2012;Ramos et al, 2013).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our results support that the favoring of few species around cage fish farms, contribute to spatial differences in fish community between fish farm and reference sites, as demonstrated by Permanova analysis. This favoring is supported by concomitantly studies performed in the same cage fish farms with the same fishes used in this study showed that opportunistic and omnivore species, like A. affinis, A. lacustris, I. labrosus, P. maculatus and S. insculpta consume the uneaten food released by fish farms, causing alterations in their numeric abundance, condition factor and reproductive period (Brandão et al, 2014;Brandão et al, 2013;Brandão et al, 2012;Ramos et al, 2013).…”
Section: Discussionsupporting
confidence: 71%
“…Historically, river damming has induced impacts like restructuring of fish communities (Araújo et al, 2013), depletion of rheophilic fishes, proliferation of small and sedentary species (Agostinho et al, 2007;Nobile et al, 2016) and introduction of non-native fish species (Gois et al, 2015). Further, the recent expansion of aquaculture in cage fish farms can act as a new source to impact fish communities in large reservoirs in Neotropical region (Brandão et al, 2014;Brandão et al, 2013;Brandão et al, 2012;Ramos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For the lentic environments, in which cages are usually installed, there are reports of drastic changes in trophic structure and in the balance of phytoplankton (Borges, Train, Dias, & Bonecker, ; Kashindye et al, ), zooplankton (Dias, Takahashi, Santana, & Bonecker, ; Terziyski, Tzavlova, Kalchev, & Iliev, ), benthos (Kashindye et al, ) and fish species (Demétrio, Gomes, Latini, & Agostinho, ; Strictar‐Pereira, Agostinho, & Gomes, ). Specifically, for ichthyofauna, the high availability of artificial food is responsible for the attraction and aggregation of fish in the vicinities of the cages resulting in changes in the structure and functioning of communities (Brandão, Santana, Ramos, & Carvalho, ).…”
Section: Introductionmentioning
confidence: 99%
“…The aggregation of fish near the cages is already recognized (Brandão et al, ); however, the mechanisms and processes responsible for this aggregation are still unknown, and more studies are needed to determine its degree of impact and its importance to wild populations. Based on this, the present study seeks to evaluate spatial and temporal variations in the fish assemblage associated with tilapia caging in a Brazilian reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on cage fish farm in freshwater systems have demonstrated changes in wild fish species on reproductive aspects of Pimelodus maculatus (Brandão et al, 2014) and influence parasitological factors in Plagioscion squamosissimus (Ramos et al, 2014). In addition, interference in settlement patterns has also been reported (Agostinho et al, 2007;Mallasen et al, 2012) due to the input of organic matter from cages and the introduction of non-native species (Zanatta et al, 2010), mainly through fish escaping from cultivation (Agostinho et al, 2007).…”
Section: Introductionmentioning
confidence: 99%